FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA SEKTOR ANEKA INDUSTRI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rosanna Purba (UNIVERSITAS SARI MUTIARA INDONESIA, 2019)
This study aims to analyze the factors that affecting the firm value in basic industrial and chemical sectors companies listed in Indonesia Stock Exchange. The factors consist of tax avoidance, information transparency and earnings management. Each factors will be tested and analyzed partially and simultaneously on the firm value. The study population was manufacturing companies listed in Indonesia Stock Exchange. The sample was basic industrial and chemical sectors companies listed in Indonesia Stock Exchange in the 2014-2017 period. The method of data collection uses purposive sampling by using of secondary data. The method used in this study is a quantitative approach, with a type of quantitative descriptive research. The statistical model used is a multiple linear regression model by SPSS program.The conclusion of this study is that partially information transparency variable influences on the firm value. Otherwise the tax avoidance and earnings management variables have no influence on the firm value. Based on the results of the simultaneous test, tax avoidance, information transparency and earnings management variables together have influence significantly on the firm value.